Modelling the passively mode-locked fiber lasers - Cheong, Si Wei (Nanyang Technological University, 2020)
Fiber laser can used widely and is popular in applications such as material processing, telecommunications, spectroscopy and medicine. With its ability to produce high output power, high optical quality, compatibility and reliability, it brands itself as one of the most adaptable and versatile devices in current market. From optoelectronics to information technology, optical solitons have become a popular topic due to their potential application. Optical solitons have proven to be a good carrier of information in high-speed communication systems. It has the capability to dismiss signal degradation by maintaining a stable pulse over long distance and thus establish itself as an attractive aspect for high speed fibreoptic transmission. To add on, the technique of mode locking is an important aspect in the production of ultrashort pulses. On top of a laser cavity and rare earth doped fiber, together with mode locking, generation of optical solitons can be attained.